2023
DOI: 10.1002/jmv.29320
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mpox and its association with sexual behavior among Chinese men who have sex with men in early August 2023

Min Du,
Min Zheng,
Jue Liu
et al.

Abstract: Study investigating mpox infection and its association with sexual behavior among men who have sex with men (MSM) in China was lacking. This observational survey aimed to provide evidence on detail characteristics of mpox cases and sexual behavior, then analyze their relationship among MSM in China to help formulate prevention and control policies. An anonymous cross‐sectional study was conducted in 27 MSM social organizations across 21 provinces, municipalities, and autonomous regions from July 31 to August 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We identified three studies meeting the inclusion criteria for question 1 (see Table 1 ). One retrospective observational study conducted in the US [ 16 ] examined contact tracing, while the other two cross-sectional studies [ 17 , 18 ] investigated specific sexual behaviours. All three studies included exclusively male participants, predominantly MSM, who self-reported their sexual behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified three studies meeting the inclusion criteria for question 1 (see Table 1 ). One retrospective observational study conducted in the US [ 16 ] examined contact tracing, while the other two cross-sectional studies [ 17 , 18 ] investigated specific sexual behaviours. All three studies included exclusively male participants, predominantly MSM, who self-reported their sexual behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Du et al. [ 18 ] investigated the association between sexual behaviour and mpox prevalence amongst men. They developed an index of safe sex behaviour based on three behaviours: condomless anal sex, commercial sex, and group sex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study reveals a concerning trend as individuals engaging in risky sexual behaviour, including activities such as having multiple partners and engaging in group sex in the past 3 months, demonstrate hesitancy in seeking medical attention or practicing self-isolate even when there is clear evidence of an increased risk of MPOX infection [ 12 , 13 , 21 ]. This highlights a gap in MPOX prevention efforts and underscores the necessity for targeted interventions to promote safer sexual practices.…”
Section: Discussionmentioning
confidence: 99%